[N] - Arantes, Paulo Tadeu (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2002)
This paper discusses intercity relations from the perspective of urban competitiveness, urban competition and urban cooperation. It does so through a description of a regional planning process carried out by a group of four southern Minas Gerais state towns – Itajubá, Santa Rita do Sapucaí, Pouso Alegre and Poços de Caldas – within the framework of urban complementarily and urban synergy. The chief purpose is to establish a new regional cooperative identity: Route 459.